Future Perspectives in Nanostructured Materials Preparation, Characteristics and Applications (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The characteristics of nanoparticles, such as their size, shape, surface morphology, crystal structure, grain boundaries, and composition, can be tuned to match the intended use. Thus, the design of nanostructured materials with a wide range of applications in the engineering, chemistry, physics, ceramics, biotechnology, biomedicine, and environmental fields represents an active area of research. Nanostructured materials are now widely used in research and industry, and their particular properties enable advanced physicochemical, electrical, thermal, catalytic, coloristic, optical, and magnetic applications.The present Special Issue aims to provide a comprehensive overview of original research articles, communications, and reviews that focus on the development, characterization, and/or applications of nanoparticles and their composites.